PERAN WANITA TANI DALAM USAHATANI CENGKEH DI DESA BAHO BUBU KECAMATAN WAWONII TIMUR LAUT KABUPATEN KONAWE KEPULAUAN - Salahuddin Salahuddin; Nurhayu Malik; Hariyanto Hariyanto (Universitas Halu Oleo, 2022)
The purposed of this studied was to examined the role of women farmers in Clove Farming in Baho Bubu Village, Northeast Wawonii District, Konawe Islands Regency. The population in this studied were all female farmers who cultivate cloves in Baho Bubu Village, Northeast Wawonii District, Konawe Islands Regency. The research sample was 36 female farmers who did clove farming which were taken by census. The results showed that the role of women farmers in clove farming in Baho Bubu Village, Northeast Wawonii District, Konawe Islands Regency was a good role in clove farming, especially in land preparation, planting, plant care and harvesting of clove farming.